Pengaruh pH Air Pelarut Herbisida Kalium Glifosat Terhadap Pengendalian Gulma Rumput Sarang Buaya (Ottochloa nodosa) - Dimas Andika; Kamsia Dorliana Sitanggang; Siti Hartati Yusida Saragih; Widya Lestari (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
Ottochloa nodosa is a type of weed that is detrimental to cultivated crops. One of the most commonly used chemical weed controls is the potassium glyphosate herbicide. This study was compiled using a random group design (RAK) with 3 levels and each treatment is repeated 6 times, thus becoming 18 plots of treatment. The treatments tested were: (P1) potassium glyphosate + solvent water pH 4, (P2) potassium glyphosate + solvent water pH 6, and (P3) potassium glyphosate + solvent water pH 8. The results showed that the pH of the water solvent herbicide Potassium Glyphosate had an effect on wet weight and dry weight of the header. Where there is the lowest header dry weight (104.67 grams) at pH use 6 and the largest header dry weight (116.80 grams) at pH use 8. Keywords : Ottochloa nodosa, Potassium Glyphose, pH water solvent